Aryl Hydrocarbon Receptor Nuclear Translocator in Vascular Smooth Muscle Cells Is Required for Optimal Peripheral Perfusion Recovery. Issue 11 (1st June 2018) - Borton, Anna Henry; Benson, Bryan L.; Neilson, Lee E.; Saunders, Ashley; Alaiti, M. Amer; Huang, Alex Y.; Jain, Mukesh K.; Proweller, Aaron; Ramirez‐Bergeron, Diana L.
Abstract : Background: Limb ischemia resulting from peripheral vascular disease is a common cause of morbidity. Vessel occlusion limits blood flow, creating a hypoxic environment that damages distal tissue, requiring therapeutic revascularization. Hypoxia‐inducible factors (HIFs) are key transcriptional regulators of hypoxic vascular responses, including angiogenesis and arteriogenesis. Despite vascular smooth muscle cells' (VSMCs') importance in vessel integrity, little is known about their functional responses to hypoxia in peripheral vascular disease. This study investigated the role of VSMC HIF in mediating peripheral ischemic responses. Methods and Results: We used Arnt SMKO mice with smooth muscle–specific deletion of aryl hydrocarbon receptor nuclear translocator (ARNT, HIF‐1β), required for HIF transcriptional activity, in a femoral artery ligation model of peripheral vascular disease. Arnt SMKO mice exhibit impaired perfusion recovery despite normal collateral vessel dilation and angiogenic capillary responses. Decreased blood flow manifests in extensive tissue damage and hypoxia in ligated limbs of Arnt SMKO mice. Furthermore, loss of aryl hydrocarbon receptor nuclear translocator changes the proliferation, migration, and transcriptional profile of cultured VSMCs. Arnt SMKO mice display disrupted VSMC morphologic features and wrapping around arterioles and increased vascular permeability linked to decreased local blood flow. Conclusions: Our data demonstrate that traditional vascular remodeling responses are insufficient to provide robust peripheral tissue reperfusion in Arnt SMKO mice. In all, this study highlights HIF responses to hypoxia in arteriole VSMCs critical for the phenotypic and functional stability of vessels that aid in the recovery of blood flow in ischemic peripheral tissues.